DIETARY LUFENURON REDUCES EGG HATCH AND INFLUENCES PROTEIN EXPRESSION IN THE FRUIT FLY Bactrocera latifrons (HENDEL). Issue 4 (21st April 2014) - Chang, Chiou Ling; Geib, Scott; Cho, Il Kyu; Li, Qing X.; Stanley, David
<x xml:space="preserve">Abstract</x> Lufenuron (LFN), a chitin synthase inhibitor, impacts the fertility of Ceratitis capitata, Bactrocera dorsalis, B. cucurbitae, and B. latifrons. We posed the hypothesis that LFN curtails egg hatch in the solanaceous fruit fly, B. latifrons. In this study, newly emerged virgin adults were sexed and fed for 12 days with varying concentrations of LFN‐laced agar diets until sexual maturation. Eggs were collected from 12‐d‐old adults and the egg hatch was assessed. Egg hatch decreased in adults reared on LFN‐treated diets. LFN‐treated media did not influence fertility after one gender was reared on experimental and the other on control media before mating. Exposure to LFN‐treated medium after mating led to reduced egg hatch. We infer that LFN is not a permanent sterilant, and reduced egg hatch depends on continuous exposure to dietary LFN after mating. Proteomic analysis identified two differentially expressed proteins, a pheromone binding protein and a chitin binding protein, between adults maintained on LFN‐treated and control diets. Expression of two genes encoding chitin synthase 2, and chitin binding protein, was altered in adults exposed to dietary LFN. LFN treatments also led to increased expression of two odorant binding proteins one in females and one in males. We surmise these data support our hypothesis and provide insight into LFN actions.